Testicular germ cell tumors: tumor grade co-relation with TNS stages and remote metastasis - Serhii M. Potapov; Nataliia I. Horhol; Daria I. Halata; Oksana M. Pliten (Kazimierz Wielki University, 2019)
The performed analysis, based on the examination of pathologists' reports and medical case histories of the patients of Kharkiv regional clinical center of urology and nephrology named after Shapovalov V.I., for the period covering years 1998-2017, is devoted to the investigation of correlation between the degree of tumorous lesion of the testes and categories of pTNM classification in patients with TGCT. According to the obtained data, there are significant differences between the different histological types of the TGCT. It is concluded that the most aggressive TGCT is embryonic cancer and yolk sac tumor, postpubertal-type; the least aggressive of all is seminoma and teratoma, postpubertal-type; the mixed TGCT hold an intermediate position.